Relationship between Moral Intelligence and Nurses' Quality of Work Life - J Mohamadi; F Ghazanfari; A Azizi (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Moral intelligence is linked with doing right work and adherence to ethics. This study aimed to investigate the relationship between moral intelligence and quality of work life of nurses in Tabriz hospitals.   Material & Methods: It was a cross-sectional descriptive correlational study. The study population consisted of all nurses working in hospitals of Tabriz in 2014. Using stratified random sampling, 186 nurses were recruited as the research sample. Lennick and Kiel's (2005) moral intelligence questionnaire and Brooks and Anderson's (2005) quality of work life survey were used to collect the data. The data were analyzed by descriptive statistics and inferential statistical methods including Pearson's correlation coefficient and regression analysis using SPSS-PC (v. 20).   Results: According to findings, there was significant positive relationships between the elements of moral intelligence and quality of work life - home, quality of work context and quality of work world (P = 0.001). There was no significant relationship between moral intelligence and quality of work design. The regression analysis showed that moral intelligence could predict the quality of work life/home life, the quality of work context and the quality of work world. However, it did not have a significant role in the prediction of quality of work design.   Conclusion: Considering that the quality of nursing work life is predictable through moral intelligence, it seems that appropriate levels of moral intelligence could lead nurses to play a significant role in hospitals. Meanwhile, approaches such as encouraging moral behavior would improve the present situation.